Development and analysis of a novel CSP source driven cogeneration cycle for the production of electric power and low temperature refrigeration. (October 2021) - Khaliq, Abdul; Refaey, H.A.; Alharthi, Mathkar A.
Highlights: New design of central receiver is proposed to enhance the rate of solar to heat conversion. Energetic and exergetic modeling is presented for the combined power and refrigeration system. DNI and coil diameter have a significant effect on variation of temperature of oil in the receiver. Performance of the system is influenced at large by the change in type of ORC working fluid. Abstract: This communication presents the implementation of a central receiver where helically coiled tubes are employed in order to enhance the rate of solar to heat conversion, which is the energy source that drives a cogeneration cycle which consists of organic Rankine cycle and the ejector-absorption refrigeration cycle. A numerical simulation with the application of computational fluid dynamics using the ANSYS-FLUENT package was conducted to examine the effect of the coil diameter and inlet oil (Duratherm 600) temperature on the pressure and temperature of solar heat transfer fluid (SHTF) which leaves the receiver. It is found that for inlet temperature of 92°C and direct normal irradiations of 850 W/m 2, the outlet temperature of solar heat transfer fluid is raised by 9% when the coil diameter increased from 150 to 400 mm. Further, cogeneration cycle response to altering operating parameters is also investigated. From 100% radiative solar energy supplied to cogeneration cycle, it is revealed that fluids of organic Rankine cycle; R141b, R600a, and R143a produce the energetic output as 20.64%, 15.04%, and 8.33%, respectively, and the remaining solar input energy is lost to environment through temperature difference. The exergy distribution shows that for R141b operated cycle out of 100% solar exergy, 16.79% is produced as exergetic output, 81.94% is the exergy destroyed, and the remaining 1.27% is the exergy loss.